A new genus and some new species of the genus Lauriea Baba, 1971 (Crustacea, Decapoda, Galatheidae) from the Pacific and Indian Oceans, using molecular and morphological characters - Macpherson, Enrique; Robainas-Barcia, Aymee (Zootaxa, 2013)
The genus Lauriea belongs to the family Galatheidae and is easily differentiated from other genera of the family by the endopod of the uropod being much wider than long and the dactyli of the walking legs being curved and strongly biunguiculate. Examination of many specimens collected during recent expeditions from Madagascar to French Polynesia and using morphological and molecular data revealed the existence of six species, five of them new, that are genetically distinct yet morphologically very similar. Furthermore, another new species, having a triunguiculate P2–4 dactyli, represents a new genus, Triodonthea.